First and Second Zagreb Coindices for Chains of Cycles - Ammar Waadallah; Ahmed Ali (Al-Rafidain Journal of Computer Sciences and Mathematics)
Abstract—The graphs which are used in this paper are simple, finite and undirected. The first and second Zagreb indices for every non-adjacent vertices (also called first and second Zagreb coindices) are dependent only on the non-adjacent vertices degrees which interspersed the operations of addition and multiplication, respectively, for the degrees of non-adjacent vertices. The number of the edges incident on vertex v in a graph G is called the degree of a vertex v and the two vertices u and v are non-adjacent if it’s no common edge between them. In this paper, we found the first and second Zagreb coindices of chains of even cycles and also, gave some examples.